Frugal Innovation and Knowledge Transferability: Innovation for Emerging Markets Using Home-Based R&DWestern firms aiming to develop products for emerging markets may face knowledge transfer barriers that favor a home-based approach to frugal innovation. Issue 1 (2nd January 2016) - Altmann, Peter; Engberg, Robert
OVERVIEW: Western firms are generally advised to rely on emerging market partners when attempting to develop frugal innovations for these developing markets. Underlying such advice is the idea that the requirements of emerging market consumers may not be familiar to Western firms and local developers will better understand local needs. We propose an alternative approach for high-tech firms—one that relies on home-based breakthrough R&D focused on emerging market needs. Three frugal innovation projects at a Swedish medical devices manufacturer serve to illustrate both how home-based breakthrough R&D can help managers reconceptualize their core products and the contextual factors favoring such an approach.